PENGARUH AKTIVASI KIMIA PERMUKAAN PASIR SILIKA TERHADAP EFISIENSI ADSORPSI TIMBAL(II) - Sani, Muhammad Irfansyah Naufal; Trihadiningrum, Yulinah; Wilujeng, Susi Agustina (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2025)
The electroplating industry has grown by 12.56% annually, increasing the risk of environmental pollution due to wastewater containing heavy metals, particularly lead (Pb), with concentrations reaching 3.56 mg/L—exceeding regulatory limits. This study aims to evaluate the efficiency of chemically activated silica sand in removing Pb(II) from synthetic solutions, determine the optimum adsorption conditions, and model the adsorption isotherm. The activation was carried out using a mixture of 98% H₂SO₄ and 30% H₂O₂, followed by neutralization and drying at 105 °C. FTIR characterization indicated enhanced hydroxyl and silanol groups, which serve as active adsorption sites. SSA analysis showed an increase in specific surface area from 11.383 to 12.356 m²/g and an expansion in pore diameter from 6.08 to 9.49 nm. XRF analysis revealed an increase in SiO₂ content from 83.1% to 89.4%, indicating higher surface purity after activation. Batch adsorption experiments showed optimum performance at pH 4. At an initial Pb(II) concentration of 25.5 mg/L, the removal efficiency reached 99.94% with an adsorption capacity of 2.553 mg/g. Meanwhile, at 55.09 mg/L, the capacity increased to 5.072 mg/g but efficiency declined. The Langmuir isotherm is the most suitable for describing the adsorption equilibrium (R² = 0.998; qmax = 7.68 mg/g). Chemical activation effectively enhanced the performance of silica sand as an efficient and economical Pb(II) adsorbent.